Predicting Dirac semimetals based on sodium ternary compounds. (December 2018) - Peng, Bo; Yue, Changming; Zhang, Hao; Fang, Zhong; Weng, Hongming
Abstract Predicting new Dirac semimetals, as well as other topological materials, is challenging since the relationship between crystal structure, atoms and band topology is complex and elusive. Here, we demonstrate an approach to design Dirac semimetals via exploring chemical degree of freedom. Based on understanding of the well-known Dirac semimetal, Na3 Bi, three compounds in one family, namely Na2 MgSn, Na2 MgPb, and Na2 CdSn, are located. Furthermore, hybrid-functional calculations with improved accuracy for estimation of band inversion show that Na2 MgPb and Na2 CdSn have the band topology of Dirac semimetals. The nontrivial surface states with Fermi arcs on the (100) and (010) surfaces are shown to connect the projection of bulk Dirac nodes. Most importantly, the candidate compounds are dynamically stable and have been experimentally synthesized. The ideas in this work could stimulate further predictions of topological materials based on understanding of existing ones. Dirac semimetals: materials discovery First-principle calculations leveraging the chemical degree of freedom are used to establish an approach for finding new Dirac semimetals, which are exciting topological materials, but challenging to identify theoretically. Hao Zhang, Hongming Weng and colleagues from different Chinese institutions propose a chemically intuitive approach to the search for new Dirac semimetals. Starting from a known material, Na3 Bi, they computationally vary the chemical composition while maintaining the crystal and electronic structure as close as possible to that of the original compound and single out three promising compounds. They also identify chemical rules that help predict whether a material will display band inversion, a key ingredient for obtaining topological properties, finding that two of the material candidates should display it. Their design strategy could be applied also to other classes of topological materials.